2009
DOI: 10.3189/002214309788608859
|View full text |Cite
|
Sign up to set email alerts
|

Production and decay of random kinetic energy in granular snow avalanches

Abstract: ABSTRACT. Any model of snow avalanches must be able to reproduce velocity profiles. This is a key problem in avalanche science because the profiles are the result of a multitude of snow/ice particle interactions that, in the end, define the rheology of flowing snow. Recent measurements on real-scale avalanches show that the velocity profiles change from a highly sheared profile at the avalanche front to a plug-like profile at the avalanche tail, preventing the application of a single, simple rheology to the av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 25 publications
2
86
0
Order By: Relevance
“…The decay, , was defined according to snow characteristics, ¼ 0:7 (Buser and Bartelt, 2009). We defined the forested regions, A f , identical to simulations with the VS model ( ¼ 0) with K -values of 10 and 30 Pa, depending on the forest structure.…”
Section: Simulations With 6 ¼mentioning
confidence: 99%
“…The decay, , was defined according to snow characteristics, ¼ 0:7 (Buser and Bartelt, 2009). We defined the forested regions, A f , identical to simulations with the VS model ( ¼ 0) with K -values of 10 and 30 Pa, depending on the forest structure.…”
Section: Simulations With 6 ¼mentioning
confidence: 99%
“…As input parameters, the model uses the release area (measured), the snowcover initial conditions (calculated) and a set of friction and avalanche parameters. The avalanche parameters were found by Buser and Bartelt (2009);Vera et al (2015); Buser and Bartelt 275 (2015). These parameters were kept constant for all 12 case studies as in .…”
mentioning
confidence: 79%
“…The parameter β defines the dissipation of free energy of the granular solid by collisions, rubbing, abrasion, etc. It can be shown that this procedure is mass and energy conserving [Buser and Bartelt, 2009].…”
Section: Free Mechanical Energymentioning
confidence: 99%